The history of women’s activism in Singapore : Persatuan Pemudi Islam Singapura (PPIS) as a case study - Alhadad, Sharifah Aishah (2017)
This paper examines the Persatuan Pemudi Islam Singapura (PPIS), a Malay/Muslim women’s organisation marginally studied in the dominant discourse of the history of women’s activism in Singapore. PPIS’s organisational principles, attitudes, and activities are examined to understand how they have defined ‘female empowerment’, while strongly identifying itself as an apolitical and social-oriented organisation. They assigned significant emphasis on women’s fulfillment of wifely and motherly roles, which translated to community progress and national well-being. The greater meaning attached to such domestic roles would locate women’s responsibilities beyond the private sphere and into the public. As such, PPIS prioritised community service by way of educating—‘empowering’—women to be good wives and mothers. Such attitudes parallel, paradoxically, both Victorian notions of femininity and Victorian feminist ideas. This paper argues that PPIS’s activities were more socially oriented, and that their apoliticalism compromised Malay/Muslim women’s political reputation.